OPTIMIZATION OF THE IMPLEMENTATION OF UNLOADING PROCESS ON MT. PAGERUNGAN IN PLAJU PORT - Simatupang, Desamen; Fitrial, Denny; Arifki Sinaga, Brian (Dinasti International Journal of Management Science, 2021)
Depreciation (losses) is a common problem and continues to occur when the ship finishes loading or unloading at the port. This problem occurs because of differences in calculations between the ship and the land where the calculation results exceed the tolerance limit given by the company. This shrinkage can occur if the temperature between the two tanks is much different. In reducing the risk of such depreciation, it is necessary to control depreciation (losses) while on board the ship. Control can be done by checking the temperature on the land tank or ship tank. The different temperatures between land tanks and ship tanks are caused by different weather and climatic factors. Depreciation control can also be done by monitoring the volume of oil on each movement of oil from land or to ships. This control aims to control oil shrinkage from the specified tolerable loss, by reducing, maintaining and tackling, thereby increasing profits for the company. No onshore tank capacity can also hamper the loading and unloading process at the port. The loading and unloading process activities at the port, especially the land side, are the full responsibility of the Loading Master, if there is no ullage in the land tank, it must confirm or contact the ship, in this case the officer in charge and the officer in charge of the cargo because otherwise it will cause overflowed in the land tank and became a new incident. The Loading Master must also stop the loading and unloading process at the port because there is no capacity in the land tank, therefore the loading and unloading process is hampered and cannot be completed on time. Because the operation of the port is not only owned by ships, in order to streamline time, the port party coordinates with the pilot and the Loading Master regarding this kind of incident, they must remove the ship and ask the ship or the captain to dock temporarily to wait until the cargo on the land tank is sold. This is because the land side cannot predict when the cargo will be moved or distributed via tank trucks, it takes 1 hour or more, sometimes days to move the cargo.